(untitled) - Runciman, Steven (Cambridge UK, 1992)
Whether the Crusades are regarded as the most romantic of Christian expeditions, or the last of the barbarian invasions, they remain one of the most exciting and colourful adventure stories in history. An army of mounted warriors, travelling with peasants, merchants and artisans, faced a journey over hostile terrain, meeting with unforeseen antagonism, desert heat, and the constant struggle to feed and water their troops and horses. Remittance from penance, a desire to see the Holy Places, or greed for the power and booty to be captured in the East spurred the crusaders on towards the prize, be it spiritual or temporal, of the Holy City of Jerusalem. Their journey's spectacular culmination was the long siege of Jerusalem, at the end of which the Crusaders, by a brilliant tactical manoeuvre, broke down its defences and poured into the city which erupted in a bloody massacre. Steven Runciman's History of the Crusades is justly acclaimed as the most complete and fascinating account of the historic journey to save the Holy Lands from the infidel.
Keywords: Crusades,Sử học; First, 1096-1099,Thời kỳ đầu, 1096-1099